Menelusuri Rekam Pajak: Pelatihan Perpajakan Pada Badan Usaha Milik Desa (BUMDes) Sukorambi Di Kabupaten Jember - Larasati, Intania Kharisma; Mulyono, Resha Dwi Ayu Pangesti; Pratiwi, Ratna Ika Putri; Putri, Riska Bunga Rosmalia (JCOMENT (Journal of Community Empowerment), 2024)
BUMDes is an economic entity in rural areas that plays a strategic role in the development and equitable distribution of the rural economy. BUMDes is also a tax subject that must fulfill all tax obligations. The BUMDes that is the focus of this service program is BUMDes Sukorambi, located in Jember Regency. Until now, there have been no efforts for training or socialization from the local government regarding Indonesia's tax system. This situation highlights the urgency of the service program designed to improve the understanding and capacity of BUMDes Sukorambi, particularly in fulfilling tax obligations based on the self-assessment principle. The service program is carried out by students from the Accounting Study Program through PPK Ormawa HMJA at the University of Jember, with the main program being ‘Smart Village Accounting and Finance’. The method of implementing this training activity includes several stages: program socialization by the Compo’ Tax Accounting Team, preparation, implementation, and evaluation. The success of the program was measured using a comparative mechanism based on pre-test and post-test results. Based on the training activities conducted, it was found that there was an improvement in the members' understanding of the tax system in Indonesia.